The Medical Law as an Independent Branch of Law: History and Development Outlook - SITDIKOVA, Lubov Borisovna; SHILOVSKAYA, Anna Leonidovna; STARODUMOVA, Svetlana Jurievna; STARODUMOVA, Svetlana Jurievna; VOLKOVA, Maria Alexandrovna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
In the article the authors consider the specificity and importance of the concept of ‘medical law’ in modern Russia. On the basis of models of the medical law theory development, the conclusion about the prospects of its development as an independent branch of law has been done. The object and methods of legal regulation of medical relations including both private and public legal relations in the sphere of health were distinguished by the authors. The relationships in the health sector, which, by their nature, were of the administrative nature, including the relations arising between doctor and patient in which the physician was the public official were analyzed in historical retrospective. Currently one can see the strengthening of the dispositive regulation in sphere of medical activity. In this regard contractual relationships are widely used in the field of not only mandatory but compulsory medical insurance. Analyzing the relationship between the concepts of ‘medical aid’ and ‘health services’ as the General and the Particular the conceptual device was formulated. Special attention was given to the promising areas of the information-analytical activities in the field of health that allows talking about the feasibility of training medical lawyers.
Keywords: law; branch of law; medicine; medical law; medical activity; medical aid; health services; medical lawyer